Optimalisasi Kompetensi dan Pemberdayaan ASN untuk Produktivitas melalui Pengembangan Karir di BKPP Semarang - Abdul Haris Salafudin; Siti Sumiati; Suharto, Sulistyo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of competence and empowerment on the work productivity of State Civil Apparatus (ASN) at the Semarang City Personnel, Education, and Training Agency (BKPP), and to examine the role of career development as a mediating variable in this relationship. The background of this study is based on the importance of professional and sustainable management of public sector human resources in order to improve the efficiency and effectiveness of public services. ASN as the backbone of the bureaucracy needs to be supported by a holistic HR management system, which not only focuses on improving individual capabilities, but also on empowerment aspects and clear career development paths. The research method uses a quantitative approach with an explanatory research type. The population in this study is all ASN in the Semarang City BKPP environment, with a sample size of 120 people. Data collection was carried out by distributing structured questionnaires, and data analysis was carried out using the Partial Least Square (PLS) method through SmartPLS software. The results of the study indicate that competencies covering the cognitive, affective, and psychomotor aspects of ASN have a positive and significant effect on work productivity. Similarly, civil servant empowerment—both structurally (access to resources, autonomy in decision-making) and psychologically (self-confidence and meaning in work)—has a significant impact on increasing productivity. Career development plays a strong mediating role, strengthening the influence of competence and empowerment on civil servant work productivity. The practical implication of this finding is the need to formulate a more integrated civil servant management policy, encompassing ongoing training, providing space for innovation, and a meritocracy-based career system. This strategy is believed to be capable of creating adaptive, professional, and productive civil servants in responding to the increasingly complex challenges of public service in the era of digital bureaucratic transformation.